An Analysis Of Structural Social Capital And The Individual’s Intention To Share Tacit Knowledge Using Reasoned Action Theory - Smith, Carol (Journal of Applied Business Research, 2017)
The sharing of tacit knowledge is important and its relationship with the development of social capital in a University of Technology is critical in the construction of a model to support and promote appropriate tacit knowledge sharing behavior. The aim of the study was to examine the relationship between structural social capital and reasoned action theory and the individual’s intention to share tacit knowledge. Structural social capital incorporates strong network ties and a high level of network resources. Specifically, the study examined the relationship strong network ties and a high level of network resources and the individual’s attitude towards sharing tacit knowledge. It further examined the relationship between the individual’s attitude towards tacit knowledge sharing, their perceived norms about tacit knowledge sharing and their intention to share tacit knowledge. The research design was a case study incorporating quantitative research (five hundred and ninety questionnaires). A model of the individual’s intention to share tacit knowledge was developed and evaluated using structural equation modeling. The results indicated that structural social capital positively affects an individual’s attitude towards tacit knowledge sharing and that the individual’s attitude towards tacit knowledge sharing positively affects their intention to share tacit knowledge.